If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(b + -1x) = 4b + ax (b * 6 + -1x * 6) = 4b + ax (6b + -6x) = 4b + ax Reorder the terms: 6b + -6x = ax + 4b Solving 6b + -6x = ax + 4b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-4b' to each side of the equation. 6b + -4b + -6x = ax + 4b + -4b Combine like terms: 6b + -4b = 2b 2b + -6x = ax + 4b + -4b Combine like terms: 4b + -4b = 0 2b + -6x = ax + 0 2b + -6x = ax Add '6x' to each side of the equation. 2b + -6x + 6x = ax + 6x Combine like terms: -6x + 6x = 0 2b + 0 = ax + 6x 2b = ax + 6x Divide each side by '2'. b = 0.5ax + 3x Simplifying b = 0.5ax + 3x
| 85+2x=110-2x | | 4r^2=10+18r | | -2x-3=15 | | b^2=-12-7b | | 5x+6y=43 | | (1-5x)(3+7x)= | | 25+20x=125 | | 6x^3-10x^2+3x-5= | | 2x-4+5x+7=31 | | r^2-20tw+4wr-5tr= | | 8x+2=62 | | 131-3x=2x+11 | | 5c-6v=8 | | 10-0.3y= | | -8x+5+7x=22 | | 49t^2-9=0 | | -77x^4-7x^3= | | Y=x^2-7x+10 | | 24a^2-20a= | | 4y^2-2y+3=0 | | 5x/3-4=16 | | 32+4y=8y | | x/5+4=6 | | 2x-(7-5x)=7 | | 2a-6=4(a+1)+9a+2 | | h(-3)=4(-3)2+7 | | g(-3)=7(-3)-2 | | g(x)=7x-2 | | 13x+95-8x=0 | | 3(5m+2)=2(m+3)+m | | -3x+19-5x=91 | | 5=2f |